The Effect Of Prediction of Financial Difficulties And Financial Performance On Stock Returns - Feryadi Rahnaen; Siti Atikah; Robith Hudaya (International Journal of Business and Quality Research, 2024)
This research aims to analyze the effect of predicted financial difficulties (Altman z-score) and financial performance (Current ratio, Debt to Equity Ratio, and Return On Assets) on stock returns. In this research, the author used an associative research method with a quantitative approach with the data source used being secondary data and sampling using purposive sampling. The sample of this research is 33 manufacturing companies in various industrial sub-sectors listed on the Indonesia Stock Exchange from 2017 - 2021. Data analysis was done using the panel data regression method and using the Eviews 10 application. This research provides results that the Altman z-score value has a negative and insignificant influence on stock returns. The liquidity (CR) and leverage (DER) variables have a positive and insignificant influence on stock returns, and the profitability ratio (ROA) variable has a positive and insignificant influence on stock returns. The findings in this research investors can maximize investment returns and minimize investment risks.